Autoestima y riesgo de embarazo en adolescentes Buenos Aires 2015 - Gomez Rosario, Margarita Elizabeth (2015)
This descriptive correlational research work, aimed to establish the relationship between the level of self esteem and pregnancy risk in adolecents of secundary school, “ Jose Antonio Encinas”. The sample consisted in 73 adolescents, data were collected by direct interview using two instruments: risk of pregnancy Test and self esteem Test. To determine the relationship between variables was use independence of criteria Chi Square Test. We come to the conclusion that 89.0 percent of adolescents have medium high self esteem level, the 5.5 percent have medium low self-esteem level. 93.2 percent have low level of pregnancy risk, 6.8 percent have high level of pregnancy risk. There is no significant statistical relationship between the variables self-esteem and risk of teen pregnancy.